The role of nutrition and pancreatic enzyme replacement therapy in children with cystic fibrosis - Muzal Kadim; William Cheng (Indonesian Nutrition Association, 2021)
Background Cystic fibrosis (CF) is an inherited genetic disorder with high mortality and morbidity. CF is strongly correlated with malnutrition due to higher energy losses, pancreatic insufficiency, chronic inflammation, higher resting energy expenditure, and feeding problems. Malnutrition in CF patients associated with worse survival. Thus, appropriate and prompt nutritional intervention should be addressed to reduced malnutrition in CF patients. Methods The literature search was performed on 9 August 2021 in four major databases such as MEDLINE, EBSCOhost, Cochrane Reviews, and Web of Sciences to find the role of nutrition and pancreatic enzyme replacement therapy in pediatrics population with cystic fibrosis. Recent findings In recent decades, early nutritional management and pancreatic enzyme replacement therapy (PERT) have been shown to improve CF patient’s outcomes. Nutrition should be given in higher calories compared to healthy individuals with close and regular nutritional status monitoring. High protein and fat diets are essential for CF patient’s overall survival. Adequate level of micronutrients should be ensured to avoid morbidity caused by micronutrients deficiency. Regular pancreatic insufficiency screening should be done annually in order to start PERT early. Further research focusing on body composition, growth chart, protein intake, and PERT are needed to further improve the management of CF patient. Conclusion Nutritional intervention and PERT play an important role in prolonging CF patient survival. Both treatments should be initiated early with nutritional status close monitoring and tailored to each individual. Collaboration with parents and children is critical to warrant that CF patients followed the dietary advice.